Influence of CTL Model by Using Monopoly Game Media to The Students’ Motivation and Science Learning Outcomes (Universitas Negeri Semarang, 2017)
The backround of research is still textual learning and limited learning media in Karanganyar Elementary School that affected to students learning outcomes. The aim of the study is to know the influence of CTL by using Monopoly game to the motivation and the science learning outcome. This study uses Quasy Experimental Research with pretest-posttest control group design. Data of the research was conducted by using multiple choice test and Questionnaire. The Data was analyzed by using descriptive analyzing, gain score and t-test. The result showed that : (1) there is the difference between the students’ learning outcomes in the teaching learning process through CTL by using Monopoly media and the students’ learning outcomes in the teaching learning process without Monopoly Media (N-Gain = 0,71); (2) there is the difference between the students’ learning outcomes in the teaching learning process through CTL by using Monopoly media and the students’ learning outcomes in the teaching learning process through CTL without Monopoly Media (tcount = 7,876 > ttable (2,042)), and The students’ learning motivation improvement of experimental class is higher than the control class, before treatment it was 51%, and after treatment it was 86%. (3) the result of Multiple linear regression test in the students’ science learning outcomes Colum was 0,000 and the students’ learning motivation Colum was 0,000. This significant result is lower than The significant 0, 05. It showed that there is effect of CTL Method by using Monopoly game media to the students’ motivation and Science learning outcomes.